KEPENTINGAN INDONESIA DALAM INDONESIA JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) TERKAIT PERIKANAN INDONESIA - Yudihartawan, I Gusti Lanang; Sushanti, Sukma; Swecawangsa, Adi (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
IJEPA is the first partnership agreement for Indonesia and Japan. IJEPA agreement, it discusses cooperation in trade in goods and services that provides benefits to both countries. But Indonesia has not got it. This research is to find what interests Indonesia has in the IJEPA. The concept used in this study refers to put forward by Morgenthau. This power or control relationship is created through coercion or cooperation. The results show that there is Indonesia having an interest in the IJEPA agreement where Indonesia hopes to reduce import duties in the fisheries sector. Until now it has not been realized like other countries, namely Thailand and Vietnam.   Keywords : IJEPA, Fisheries, National Interest.